KALIMAT PERINTAH DALAM BAHASA GESER DI DESA KELLU KECAMATAN SERAM TIMUR MALUKU - Kelley, Anita; da Costa, Romilda Arivina; Hiariej, Chrissanty (Universitas Pattimura, 2025)
Command sentences are sentences that expect a response in the form of action from the person being spoken to. This research aims to describe the types of verbal command sentences spoken by the community in Kellu Village, East Seram District, Maluku. A descriptive qualitative approach was used in this research with an observation method supported by recording and recording techniques. The data collected is in the form of a series of words that are identified as command sentences. From this research, most of the command sentences in the Geser language are actual command sentences, invitation sentences, invitation sentences, and prohibition sentences. From the number of clauses, the Geser language command sentences show a balance of a series of sentences with a single clause and command sentences with more than one clause. Apart from that, command sentences in Geser language do not have particles to refine commands like -lah in Indonesian. However, the Geser language has a command refiner in the form of the word loka 'already'.